Household composition, routine activity, and victimization: A comparative analysis - Maxfield, Michael G. (Journal of quantitative criminology, 1987)
Adults living in single-parent households report high rates of personal and household victimization. Data from the 1982 British Crime Survey and from the 1983 Victim Risk Supplement to the U.S. National Crime Survey are used to determine whether this higher risk is due to particular patterns of routine activity among members of single-parent households. Findings indicate that these persons are disproportionately victimized by present or former spouses. Often unemployed, they are at greatest risk in the home domain. Deleting close prior relationship incidents eliminates the effects of household composition on personal victimization and produces logit models that are similar for the U.S. and British surveys.